Efektifitas Penggunaan Arabic Words Quiz dalam Meningkatkan Kemampuan Kosakata Bahasa Arab pada Siswa MIN 2 Kutai Kertanegara - Mustamin Mustamin; Muh Anhar; Nurhayati Nurhayati (Faculty of Education and Teacher Training of UINSI Samarinda, 2019)
In learning Arabic, it does not only require knowledge of Arabic grammar. However, we also have to learn and reproduce the Arabic language mufradat. By multiplying Arabic mufradat, it will be easier for someone to improve their mastery of Arabic mufradat, by using Arabic words quiz software so they don't get bored. This study aims to determine whether it is effective to use Arabic words quiz software media to improve Arabic mufradat mastery of fifth grade students at MIN 2 Kutai Kartanegara. This research is an experimental research. The research subjects were 56 students who were divided into two classes, namely class 5A as the experimental class and class 5B as the control class. The research instrument is a test for pre-test and post-test. The analytical technique used was the Mann Whitney U test which was completed with the help of the SPPS 25 computer program. The results showed that there was a significant difference between the average value of the experimental class and the control class. The results of data analysis show that the results of mastery of Arabic mufradat using conventional methods have a better average value than the Arabic word quiz software media. The average pre-test value of the experimental class was 81.79, while the average value of the control class was 76.83 and the post-test average value of the experimental class was 84.79. the control class test was 82.23. The results of the mann whitney u test applied in this study with a significant value of 0.357> 0.05, then the results are not normal. Referring to the results of data analysis and research findings, it can be concluded that the Arabic word quiz software media is not effective in mastering Arabic mufradat in class V at Madrasah Ibtidaiyah Negeri 2 Kutai Kartanegara.